SAMPAH LAUT TANGGUNG JAWAB SIAPA? STUDI KASUS KABUPATEN ACEH BARAT - Kusumawati, Ika (Universitas Teuku Umar, 2019)
Marine litter is solid material that has been used by people and abandoned or discarded into sewage, river, sea or marine environment. Debris problem in coastal area becomes the urgent issue and concerns many countries across the world particularly marine countries such as Indonesia. The research objective is to examine people perception towards marine litter in Aceh Barat Regency about whom responsible for eradicating marine debris. Researchers conduct the study in January to June 2018 and collect data by distributing questionnaire to 383 respondents. The result shows that 46.2% respondents believe that business activities in coastal area like cafe, hotel, and other business related to marine tourism responsible for keeping the sea clean. In similar, researchers find 38.6% respondent stated that elaminating marine debris is society duty starts from us. The final finding is 36.8% sample shows that researchers are the most motivated stakeholders for reducing marine litter.